Faktor-Faktor Pendorong Motivasi Dan Perannya Dalam Mendorong Peningkatan Kinerja: Tinjauan Pustaka - Akbar Abbas, Subhan (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2023)
In order for a company to achieve maximum results in terms of productivity, it needs to perform well. One of the factors that can affect performance is motivation, which is frequently studied as a factor that can affect performance. An individual's motivation can be defined as an urge to act, work, and accomplish something that arises from within. Motivation can be influenced by the desire, the need, and the desire to gain a sense of security about many things, including the work itself. In addition to these factors, there are also external factors that may be influencing motivation, such as the environment and co-workers, leadership attitudes, and incentives offered. As part of this research, a literature review is conducted to examine what factors can affect motivation as well as how motivation influences performance and plays a role in improving it. Based on the results of this study, it is clear that motivation is influenced by internal factors of a person, which include psychological factors, as well as external factors such as salary and incentives, which are also important factors that influence performance. It is important to understand that motivation plays a crucial role in supporting performance by allowing a person to work more effectively and efficiently.